2017
DOI: 10.24294/ti.v1.i3.127
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine in lupus erythematosus, a new horizon of the old drug

Abstract: CITATIONFurukawa F. Hydroxychloroquine in lupus erythematosus, a new horizon of the old drug. Trends Immunother 2017; 1(3): 99-100.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Various treatments are known in AT and alopecia universalis (AU), and although however certain treatments have shown significant hair regrowth, no treatment is completely effective [4] . Recently, the efficacy of hydroxychloroquine [5,6] in the treatment of AT has been reported [7] but its use for extensive alopecia areata is still controversial [8] . Tofatinib is also reported to show efficacy in severe AA including AT and AU [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Various treatments are known in AT and alopecia universalis (AU), and although however certain treatments have shown significant hair regrowth, no treatment is completely effective [4] . Recently, the efficacy of hydroxychloroquine [5,6] in the treatment of AT has been reported [7] but its use for extensive alopecia areata is still controversial [8] . Tofatinib is also reported to show efficacy in severe AA including AT and AU [9] .…”
Section: Discussionmentioning
confidence: 99%
“…However, our recent experiments of mast cells suggested that mast cells are biphasic-reaction in the skin lesions [7,8] . The HCQ effects on mast cell biology will be expected for better treatment of CLE [9] . …”
Section: Discussionmentioning
confidence: 99%
“…HCQ is an old and new drug. It has a long history of use, and it is only recently that one of its mechanisms has been clarified from the perspective of immunity [23] . This drug has a wide range of ac-tions such as anti-inflammatory action, immunomodulatory action, antimalarial action, and antitumor action.…”
Section: Action Mechanisms Of Hydroxychloroquinementioning
confidence: 99%